Perancangan Media Pembelajaran Berbasis Android "Pinter.In" untuk MIN 1 Jembrana - Darmawan, Ahmad Edi (Widyadewata, 2025)
This study aims to develop an Android-based learning media application "Pinter.In" to improve the quality of education at MIN 1 Jembrana. The method used is Research and Development (R&D) with the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, the learning needs were identified through observations and interviews. The design stage involved planning the main features of the application, such as an online library, interactive quizzes, educational games, and artificial intelligence (AI) technology. The development stage involved creating the application according to the planned design, followed by implementation to test its effectiveness in the school environment. The implementation results showed that the "Pinter.In" application had a positive impact on increasing student motivation and academic performance. The average academic score of students increased by 24%, with positive responses to the interactive and adaptive features. Teachers also experienced greater efficiency in managing learning, including the ease of monitoring student progress digitally. The evaluation of the application produced feedback used to refine the features and content, making "Pinter.In" a relevant and innovative learning media. In conclusion, the "Pinter.In" application successfully created an interactive, adaptive, and effective learning experience, making a significant contribution to improving the quality of education in the digital era. This application not only supports students in their learning but also facilitates teachers in managing the learning process, making it a potential solution for integrating technology into education.